Broad spectrum O-linked protein glycosylation in the human pathogen Neisseria gonorrhoeae - Vik, Åshild (National Academy of Sciences, 2009)
Protein glycosylation is an important element of biologic systems because of its significant effects on protein properties and functions. Although prominent within all domains of life, O-linked glycosylation systems modifying serine and threonine residues within bacteria and eukaryotes differ substantially in target protein selectivity. In particular, well-characterized bacterial systems have been invariably dedicated to modification of individual proteins or related subsets thereof. Here we characterize a general O-linked glycosylation system that targets structurally and functionally diverse groups of membrane-associated proteins in the Gram-negative bacterium Neisseria gonorrhoeae, the etiologic agent of the human disease gonorrhea. The 11 glycoproteins identified here are implicated in activities as varied as protein folding, disulfide bond formation, and solute uptake, as well as both aerobic and anaerobic respiration. Along with their common trafficking within the periplasmic compartment, the protein substrates share quasi-related domains bearing signatures of low complexity that were demonstrated to encompass sites of glycan occupancy. Thus, as in eukaryotes, the broad scope of this system is dictated by the relaxed specificity of the glycan transferase as well as the bulk properties and context of the protein-targeting signal rather than by a strict amino acid consensus sequence. Together, these findings reveal previously unrecognized commonalities linking O-linked protein glycosylation in distantly related life forms.